Sibling-controlled study of the impact of dietary therapy on the gut microbiota in children with phenylketonuria - Ohmi-Shimizu, Natsuki; Takano, Chika; Tsuji, Noriko M.; Iwama, Motoko; Okamura, Naoko; Komine-Aizawa, Shihoko; Hayakawa, Satoshi; Ogawa, Erika; Morioka, Ichiro; Ishige, Mika (Frontiers in Nutrition, 2026)
BackgroundPhenylketonuria (PKU) is an autosomal recessive metabolic disorder caused by a deficiency of phenylalanine hydroxylase activity. Due to intolerance to the dietary intake of phenylalanine (Phe), the patients need to take a low-protein diet alongside immediate utilization of Phe-free medical formula upon diagnosis to maintain optimal plasma Phe concentrations. While dietary influences on gut microbiome composition are well-established, the potential alterations in microbiota and their impact on the immune function of children with PKU remain underexplored. We therefore conducted a pilot, sibling-controlled study to assess how dietary therapy for PKU affects gut microbiota and whether these changes are associated with food allergy incidence.Materials and methodsA questionnaire-based survey was conducted across multiple institutions to determine the prevalence of food allergies in children with PKU. Four children with PKU who have unaffected siblings were recruited to investigate their dietary intake and immunological profiles. Stool samples from both groups were collected and analyzed for gut microbiota composition and short-chain fatty acid (SCFA) profiles.ResultsThe survey indicated a notably low prevalence of food allergies in children with PKU (approximately 1%). The four children with PKU strictly adhered to a low-protein diet and maintained their blood phenylalanine levels within the target therapeutic range. Among the PKU group, only one child had an egg allergy, while the remaining children showed no allergic tendencies. Although no adverse immunological effects were observed, the gut microbiota composition of the PKU group significantly differed from that of the unaffected siblings, as indicated by the weighted UniFrac distance (p = 0.027). In the PKU group, the abundance of Faecalibacterium prausnitzii was significantly reduced (p = 0.002), that of Bifidobacterium was increased, and Akkermansia muciniphila was detected. No overall decrease in total SCFA levels was observed in the PKU group, although the acetate/butyrate ratio significantly increased.DiscussionThis study is the first to characterize the gut microbiota of children with PKU using their unaffected siblings as genetically and environmentally matched controls. Our findings suggest that the distinctive dietary management in PKU results in a characteristic gut microbial profile. We further propose a novel hypothesis that these compositional shifts may establish a unique intestinal microenvironment in diet-adherent PKU, which could be negatively associated with the development of food allergy. Larger cohort studies incorporating host metabolomic profiling are needed to determine causal links between dietary therapy and immunological background, ultimately contributing to improved nutritional management.